PERILAKU MEMILIH SANTRI DI KABUPATEN DEMAK DALAM PEMILIHAN GUBERNUR JAWA TENGAH 2018 - Mila Amalia; Wachid Abdulrahman (Journal of Politic and Government Studies, 2019)
The religious sentiment that occurred at the end of 2017 seemed to have an impact on the political dynamics in Indonesia, and continued in the next political year, one of which was the party of democracy in Central Java. At that time the 2018 Central Java Pilgub was motivated by a political map that tended to be nationalist-religious and scrambled for votes among the Muslim community. Santri is one of the elements of the Muslim social class. Bothsides are from among the santri, namely Taj Yasin and Ida Fauziyah. The researchers were trying todo research on santri and were aiming to determine the level of participation and voting behavior of santri in Demak Regency in the 2018 Central Java’s governor election. This study used a quantitative method with a descriptive type of research.. The research was located in Demak Regency with cluster random sampling technique to determine the samples, and 96 respondents were taken as samples. Then the research data collection uses a questionnaire and literature study instrument. The results showed that the level of participation of santri in Demak Regency in the 2018 Central Java election was low. Abstentions are still high. Then psychologically the santri in Demak Regency are mostly classified as the